LIBERDADE, IGUALDADE E TRIBUTAÇÃO: uma equação necessária - OLIVEIRA, Izabella dos Santos Jansen Ferreira de (2016)
The inclusion of taxation in the context of fundamental rights raises the need to balance the values of liberty and equality, from both perspectives, the citizen and the State. This work will focus the issue using the theories of justice, especially the one developed by John Rawls (and others built after it), to analyze the necessary limitations on the power the State has to tax based on constitutional intention to build a free, fair and equitable society. Considering the need for development of the citizen as an autonomous individual, with the same value as others and the right to a plan of life, the ability to pay is understood as an important limit to the taxing power of the state on a democratic context. Beyond the individual's financial ability to bear the tax burden, fiscal capacity rises as a metacapacity for its instrumental profile to acquire liberties and features, which can characterize a free individual, of equal value and much more able to contribute to the community.